Pendekatan Holistik dalam Manajemen Pembelajaran Siswa pada Kelompok Bermain Dharma Wanita Manduro Mojokerto - Dwi Rahmawati; Wahyu Syafa'at; Elly Ermawati; Ulul Mudakir (Al-Muttaqin : Jurnal Studi, Sosial, dan Ekonomi, 2025)
This study aims to analyze the holistic approach in student learning management at Dharma Wanita Manduro Playgroup, Mojokerto. The main focus is on the implementation of integrative holistic development services, active and enjoyable learning activities tailored to children's developmental stages, and collaboration with parents and the community. The research method used is descriptive qualitative approach, involving observation, interviews, and document analysis. The results indicate that a holistic approach can enhance children's overall potential, including physical, emotional, social, and intellectual aspects. The key implication of this study is the importance of integrated learning management to support optimal early childhood development in educational institutions.